2005
DOI: 10.3349/ymj.2005.46.5.597
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Cell Cycle Regulation in Cervical Carcinoma

Abstract: Carcinoma of the uterine cervix is one of the most common malignancies among women worldwide. Human papillomaviruses (HPV) have been identified as the major etiological factor in cervical carcinogenesis. However, the time lag between HPV infection and the diagnosis of cancer indicates that multiple steps, as well as multiple factors, may be necessary for the development of cervical cancer. The development and progression of cervical carcinoma have been shown to be dependent on various genetic and epigenetic ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
69
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 102 publications
4
69
0
1
Order By: Relevance
“…43 This is in agreement with Andl et al, 5 who suggested that E7 might overcome the need for cyclin D1 in the G1 phase of the cell cycle, because it interacts with the cyclin D1-binding site on pRb. 7,44 Indeed, high expression levels of cyclin D1 were predominantly observed in HPV-negative tonsillar carcinomas, most probably pointing to cyclin D1 gene amplification in these cases.…”
Section: Discussionmentioning
confidence: 98%
“…43 This is in agreement with Andl et al, 5 who suggested that E7 might overcome the need for cyclin D1 in the G1 phase of the cell cycle, because it interacts with the cyclin D1-binding site on pRb. 7,44 Indeed, high expression levels of cyclin D1 were predominantly observed in HPV-negative tonsillar carcinomas, most probably pointing to cyclin D1 gene amplification in these cases.…”
Section: Discussionmentioning
confidence: 98%
“…[23][24][25] The reasons for these discrepancies are not entirely clear although variations in immunohistochemical techniques and interpretation of staining results may be relevant. 26 It is also notable that some investigations have shown increased cyclin D1 mRNA in a proportion of intraepithelial or invasive cervical neoplasms in the absence of protein expression, suggesting that posttranscriptional mechanisms such as protein degradation may be important in some cases. 18,27 Nevertheless, it seems that decreased cyclin D1 expression is a common event in cervical neoplastic lesions of both squamous and glandular subtype.…”
Section: Discussionmentioning
confidence: 99%
“…ARID3A also interacts with p53 and is involved in the p53 regulatory pathway, suggesting that ARID3A plays a role in growth suppression mediated by p53 (35). In addition, p14ARF inhibits formation of the MDM2-p53 complex and subsequently prevents MDM2-induced p53 degradation (36). p14ARF stops cell growth at the G1/S and G2/M phases (36).…”
Section: Identification Of Arid-containing Proteins and Arid1a-interamentioning
confidence: 99%
“…In addition, p14ARF inhibits formation of the MDM2-p53 complex and subsequently prevents MDM2-induced p53 degradation (36). p14ARF stops cell growth at the G1/S and G2/M phases (36). Loss of the p53 signaling pathway occurs in human cancer either by p53 gene mutation (a direct mechanism) or by loss of cell signaling upstream and downstream of p53 (an indirect mechanism) in the remaining cancers expressing wild-type p53 gene (37).…”
Section: Identification Of Arid-containing Proteins and Arid1a-interamentioning
confidence: 99%
See 1 more Smart Citation